Pengaruh Good Corporate Governance terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Mediasi - Dandy Christian Vieri; Witis Anggraito; Rohmawati Kusumaningtias; Ambar Kusumaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research conducts an analysis of the impact of Good Corporate Governance (GCG) implementation on industry value, with profitability serving as a connecting variable in manufacturing industries listed on the Indonesia Stock Exchange (IDX) throughout the period 2016 to 2020. GCG is assessed through several aspects, namely the size of the board of commissioners, the proportion of independent commissioners, management ownership, institutional ownership, and the existence and quality of the audit committee. Profitability is measured using Return on Assets (ROA) and Return on Equity (ROE), while industry value is evaluated using Tobin's Q and Price to Book Value (PBV). Illustrations were taken using a purposive sampling method, creating 10 manufacturing industries that met certain criteria. To test the direct and indirect effects of GCG on industry value through profitability, path analysis was used with the Baron and Kenny approach and the Sobel test.